Surgical Techniques for Revascularization in Abdominal Wall Transplantation - Atia, Andrew; Hollins, Andrew; Shammas, Ronnie; Phillips, Brett T.; Ravindra, Kadiyala V.; Sudan, Debra L.; Giele, Henk; Mithani, Suhail K.; Erdmann, Detlev (Journal of Reconstructive Microsurgery, 2020)
Background Abdominal wall vascularized composite allotransplantation (AW-VCA) can be considered as a technically feasible option for abdominal wall reconstruction in patients whose abdomen cannot be closed using traditional methods. However, successful initial abdominal wall revascularization in the setting of visceral organ transplantation can pose a major challenge as graft ischemia time, operating in a limited surgical field, and variable recipient and donor anatomy must be considered. Several techniques have been reported to accomplish abdominal wall revascularization.Methods A literature review was performed using PubMed for articles related to “abdominal wall transplantation (AWT).” The authors of this study sorted through this search for relevant publications that describe abdominal wall transplant anatomy, technical descriptions, and outcomes of various techniques.Results A total of four distinct revascularization techniques were found in the literature. Each of these techniques was described by the respective authors and reported varying patient outcomes. Levi et al published a landmark article in 2003 that described technical feasibility of AWT with anastomosis between donor external iliac and inferior epigastric vessels with recipient common iliac vessels in end-to-side fashion. Cipriani et al described a microsurgical technique with anastomosis between donor and recipient inferior epigastric vessels in an end-to-end fashion. Giele et al subsequently proposed banking the abdominal wall allograft in the forearm to reduce graft ischemia time. Recently, Erdmann et al described the utilization of an arteriovenous loop for synchronous revascularization of abdominal wall and visceral transplants for reduction of ischemia time, operative time, while eliminating the need for further operations.Conclusion Vascularized composite allotransplantation continues to advance with improving immunotherapy and outcomes in solid organ transplantation. Optimizing surgical techniques remains paramount as the field continues to grow. Refinement of the presented methods will continue as additional evidence and outcomes become available in AW-VCA.
Keywords: abdominal wall transplantation; vascularized composite allotransplantation; microsurgery; abdominal wall reconstruction; revascularization